The Influence of Price Value, E-WOM, Subjective Norm, Perceived Behavior Control on Online Purchase Intentions through Attitude - Purwianti, Lily; Jason, Jason; Yulianto, Edy (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
This research examines the mediating role of consumer attitudes in using e-commerce applications in Indonesia and their relationship with price value, E-WOM, subjective norm, perceived behavior control on online purchase intention. This study shows that price value, E-WOM, subjective norm, and perceived behavior control have a significant direct effect on attitude. Attitude also has a significant direct effect on online purchase intention. The indirect relationship in this study has been known that price value, E-WOM, subjective norm, and perceived behavior control through attitude mediation have a significant effect on online purchase intention. The objective of this research is to expand research by analyzing attitude as a mediating variable between price value, subjective norm, perceived behavior control and online purchase intention. The implications of this study suggest that e-commerce users gain knowledge to choose the right e-commerce platform, transaction security in e-commerce applications, and can compare the prices of products offered with market prices or with other e-commerce applications.